Discovery of the bifunctional modulator of angiotensin II type 1 receptor (AT1R) and PPARγ derived from the AT1R antagonist, Fimasartan. Issue 19 (15th October 2018) - Choung, Wonken; Jung, Hui Jin; Nam, Eun Hye; Yang, Deokmo; Yoo, Byoungwook; Choi, Hyukjoon; Lee, Bo Ram; Park, Min; Jang, Su Min; Lim, Jae Soo; Kim, Kyung-Hee; Chin, Jungwook; et al.
Graphical abstract: Highlights: A lead compound with dual activity for PPARγ and AT1R has been identified. Extensive SAR on antihypertensive Fimasartan led to the lead, Compound18 . Lead has proved its POC in animal models of type 2 diabetes and hypertension, respectively. Abstract: Inspired by the well-known PPARγ partial agonism of angiotensin II type 1 receptor (AT1R) antagonists exemplified by an antihypertensive drug, Telmisartan, efforts to identify compounds with the dual activities have been pursued in order to control the two major metabolic disorders, hypertension and hyperglycemia simultaneously. Lead compound 18 derived from the AT1R antagonist, Fimasartan, has successfully presented the possibility to control the medical conditions by a single molecule.